Silicon-based material, electrochemical device and electronic equipment
Through the combination technology of silicon carbon materials and silicon oxygen materials, the problem of degradation of energy density and circulation performance caused by volume expansion of silicon materials in lithium-ion batteries is solved, and the high energy density and good circulation performance of lithium-ion batteries are achieved.
Patent Information
- Application Number
- CN202411349028.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-26
AI Technical Summary
The silicon material in lithium-ion batteries will cause large volume expansion and contraction during the embedding process, resulting in a decrease in the energy density and cycling performance of lithium-ion batteries, and it is difficult for the existing technology to effectively solve this problem.
Using the combination technology of silicon carbon materials and silicon oxygen materials, by controlling their average particle size ratio (D150/D250) and mass percentage content, combined with the appropriate silicon and oxygen element content, amorphous silicon structure and nanoscale Si groups are formed. cluster, improve electrochemical and expansion properties.
It significantly improves the volume energy density and kinetic performance of lithium-ion batteries, improves the circulation and expansion performance, and enhances the temperature coefficient and rate performance of lithium-ion batteries.
Smart Images

Figure CN119230781A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical energy storage, and in particular to a silicon-based material, an electrochemical device, and an electronic device. Background Art
[0002] Electrochemical devices, such as lithium-ion batteries, have the characteristics of high specific energy, high operating voltage, low self-discharge rate, small size, and light weight, and are widely used in the field of consumer electronics. With the rapid development of electric vehicles and mobile electronic devices, people have higher and higher requirements on the energy density, safety, and cycle performance of lithium-ion batteries. Among them, silicon materials have a high theoretical gram capacity (4200mAh / g), and their application in lithium-ion batteries has broad prospects.
[0003] However, when lithium ions are embedded in the negative electrode, the silicon material will produce a large volume expansion and contraction, consume lithium ions and electrolyte in the lithium-ion battery, and even cause the negative electrode material to rupture, seriously affecting the energy density and cycle performance of the lithium-ion battery. Therefore, it is urgent to find a negative electrode material with a higher energy density to improve the cycle performance and expansion performance of lithium-ion batteries. Summary of the invention
[0004] The purpose of this application is to provide a silicon-based material, an electrochemical device, and an electronic device to improve the volume energy density, cycle performance, and storage performance of the electrochemical device. The specific technical solution is as follows:
[0005] It should be noted that in the invention content of the present application, the present application is explained by taking a lithium-ion battery as an example of an electrochemical device, but the electrochemical device of the present application is not limited to a lithium-ion battery.
[0006] The first aspect of the present application provides a silicon-based material, the silicon-based material includes a silicon-carbon material and a silicon-oxygen material, and the average particle size D150 of the silicon-carbon material and the average particle size D250 of the silicon-oxygen material satisfy: 1.8 <D150 / D250<10。
[0007] In one embodiment of the present application, D150 is 4 μm to 10 μm, and D150 is preferably 6 μm to 8 μm.
[0008] In one embodiment of the present application, D250 is 0.8 μm to 3.5 μm, and D250 is preferably 1.5 μm to 2.5 μm.
[0009] In one embodiment of the present application, based on the mass of the silicon-based material, the mass percentage of the silicon-carbon material is W1, the mass percentage of the silicon-oxygen material is W2, and the mass percentage of the silicon-carbon material is W3. <W1 / W2<16。
[0010] In one embodiment of the present application, based on the mass of the silicon-based material, the mass percentage W1 of the silicon-carbon material is 70% to 95%, and the mass percentage W2 of the silicon-oxygen material is 5% to 30%.
[0011] In one embodiment of the present application, based on the mass of the silicon-carbon material, the mass percentage of silicon in the silicon-carbon material is 40% to 51%, and the mass percentage of carbon in the silicon-carbon material is 45% to 57%.
[0012] In one embodiment of the present application, based on the mass of the silicon-oxygen material, the mass percentage of silicon in the silicon-oxygen material is 50% to 56%, and the mass percentage of oxygen in the silicon-oxygen material is 32% to 41%.
[0013] In one embodiment of the present application, in the Raman spectrum of the silicon-based material, I A Indicates 521cm in the Raman spectrum -1 ±15cm -1 The intensity of the peak A at B Indicates 480cm in the Raman spectrum -1 ±15cm -1 The intensity of the B peak at 0.85 A / I B <1.4.
[0014] In one embodiment of the present application, the grain size D1 of silicon crystallites in the silicon-carbon material is less than 2.5 nm.
[0015] In one embodiment of the present application, there is a crystallization peak of silicon in the X-ray diffraction spectrum of the silicon-oxygen material, and the grain size D2 of silicon crystallites in the silicon-oxygen material is 1.6 nm to 5 nm.
[0016] In one embodiment of the present application, a ratio D1 / D2 of a grain size of silicon microcrystals in the silicon-carbon material to a grain size of silicon microcrystals in the silicon-oxygen material is 0.29 to 0.67.
[0017] In one embodiment of the present application, the compacted density of the silicon-based material is 1.0 g / cm 3 Up to 2.2g / cm 3 .
[0018] The second aspect of the present application provides an electrochemical device, which includes a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte. The negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector, and the negative electrode material layer includes the silicon-based material in any of the aforementioned embodiments.
[0019] A third aspect of the present application provides an electronic device, which includes the electrochemical device in any of the aforementioned embodiments.
[0020] Beneficial effects of this application:
[0021] The silicon in silicon-carbon materials exists in the form of amorphous silicon, with high gram capacity and initial efficiency, and good cycle performance. The silicon-oxygen material is composed of many uniformly distributed nano-scale Si clusters, SiO2 clusters, and SiO clusters. During the charge and discharge process, the Li2O matrix surrounds the Li x The Si core can act as a fast diffusion channel for lithium ions, while the Li x The Li2O and Li4SiO4 matrices around the Si core can also effectively release the stress caused by expansion, with relatively small volume changes and good dynamics. By compounding large-particle silicon-carbon materials with small-particle silicon-oxygen materials, when D150 / D250 is within the scope of this application, the pores left by the silicon-carbon materials can be appropriately filled, thereby improving the compaction density and the contact between the particles, while taking into account the electrochemical performance, and improving the volume energy density and dynamic performance of the lithium-ion battery. By controlling the ratio of D150 / D250 and compounding silicon-carbon materials and silicon-oxygen materials of appropriate particle sizes, the temperature coefficient, cycle performance and expansion performance of lithium-ion batteries can be improved, while the volume energy density of lithium-ion batteries can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.
[0023] Figure 1 This is the Raman spectrum of the silicon-based material of Example 2-1 of the present application. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0025] It should be noted that in the specific embodiments of the present application, a lithium-ion battery is used as an example of an electrochemical device to explain the present application, but the electrochemical device of the present application is not limited to a lithium-ion battery.
[0026] The first aspect of the present application provides a silicon-based material, which includes a silicon-carbon material and a silicon-oxygen material. The average particle size D150 of the silicon-carbon material and the average particle size D250 of the silicon-oxygen material satisfy: 1.8 < D150 / D250 < 10, where D150 is from 4 μm to 10 μm. For example, D150 / D250 can be 1.8, 2, 3, 4, 5, 6, 7, 8, 9, 10 or a range composed of any two of these values. Without being limited to any theory, the inventors of the present application found that the silicon in the silicon-carbon material exists in the form of amorphous silicon, which has a high specific capacity and initial efficiency and good cycling performance. The silicon-oxygen material is composed of many uniformly distributed nanoscale Si clusters, SiO2 clusters, and SiO clusters. During the charge and discharge process, the Li2O matrix surrounds the Li x The Si core can act as a fast diffusion channel for lithium ions, and the Li2O and Li4SiO4 matrices around the LixSi core can also effectively release the stress caused by expansion, with relatively small volume changes and good kinetics. By compounding a large-particle-size silicon-carbon material with a small-particle-size silicon-oxygen material, when D150 / D250 is within the range of the present application, the pores left by the silicon-carbon material can be appropriately filled, thereby improving the tap density and the contact between particles. While taking into account the electrochemical performance, the volumetric energy density and kinetic performance of the lithium-ion battery are improved. When the value of D150 / D250 is too low, the particle sizes of the silicon-carbon material and the silicon-oxygen material are relatively close, and it is difficult for the silicon-oxygen material to fill the pores between the silicon-carbon materials. Moreover, the capacity of the silicon-oxygen material itself is less than that of the silicon-carbon material, which is not conducive to improving the volumetric energy density of the battery; when it is too high, the particle size of the silicon-carbon material is too large and / or the particle size of the silicon-oxygen material is too small, which is not conducive to the conduction of electrons and ions, and the fine particles will also consume more electrolyte, which is not conducive to the battery cycle. By controlling the ratio of D150 / D250 and compounding silicon-carbon materials and silicon-oxygen materials with appropriate particle sizes, the temperature coefficient, cycling performance, and swelling performance of the lithium-ion battery can be improved, and at the same time, the volumetric energy density of the lithium-ion battery can be increased.
[0027] The average particle size D150 of the silicon-carbon material is from 4 μm to 10 μm, preferably from 6 μm to 8 μm. For example, the average particle size D150 of the silicon-carbon material can be 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm or a range composed of any two of these values. If the particle size of the silicon-carbon material is too small, the surface area is relatively larger, and the active lithium ions consumed during the first lithium deintercalation process increase, which will reduce the initial Coulomb efficiency; if the particle size of the silicon-carbon material is too large, the transmission paths of electrons and lithium ions are too long, which will lead to a decrease in kinetic performance. When the average particle size D150 of the silicon-carbon material is within the above range, the small particles in the system can fill the voids between the large particles, which helps to increase the tap density of the electrode sheet and the rebound compaction of the battery, thereby improving the volumetric energy density and kinetic performance of the lithium-ion battery.
[0028] In an embodiment of the present application, the average particle size D250 of the silicon-oxygen material is 0.8 μm to 3.5 μm, preferably 1.5 μm to 2.5 μm. For example, the average particle size D250 of the silicon-oxygen material can be 0.8 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, or a range composed of any two of these values. When the average particle size D250 of the silicon-oxygen material is within the above range, it can reduce the active lithium ions consumed during the lithium deintercalation process, improve the initial Coulombic efficiency, shorten the transmission paths of electrons and lithium ions, improve the kinetic performance of the lithium-ion battery, and the small particles in the system can fill the voids between the large particles, which helps to increase the compaction density of the electrode sheet and the rebound compaction of the battery, thereby improving the volumetric energy density and kinetic performance of the lithium-ion battery.
[0029] The present application does not particularly limit the particle classification technology, as long as the purpose of the present application can be achieved. The particle classification technology can be any known classification means in the art used, such as air classification or cyclone classification. In the present application, D50 refers to the particle size at which, in the particle size distribution based on the volume of the material, starting from the small particle size, the cumulative volume reaches 50%.
[0030] In an embodiment of the present application, based on the mass of the silicon-based material, the mass percentage content of the silicon-carbon material is W1, and the mass percentage content of the silicon-oxygen material is W2, and 2.9 < W1 / W2 < 16. For example, W1 / W2 can be 2.9, 4, 6, 8, 10, 12, 14, 16, or a range composed of any two of these values. When the value of W1 / W2 is within the above range, by controlling the different mass ratios of the silicon-carbon material and the silicon-oxygen material, the pores between the particles can be regulated, and while taking into account the cycle performance and expansion performance of the lithium-ion battery, the volumetric energy density is improved.
[0031] In an embodiment of the present application, based on the mass of the silicon-based material, the mass percentage content W1 of the silicon-carbon material is 70% to 95%, and the mass percentage content W2 of the silicon-oxygen material is 5% to 30%. For example, the mass percentage content W1 of the silicon-carbon material can be 70%, 75%, 80%, 85%, 90%, 95%, or a range composed of any two of these values; the mass percentage content W2 of the silicon-oxygen material can be 5%, 10%, 15%, 20%, 25%, 30%, or a range composed of any two of these values. When the mass percentage content W1 of the silicon-carbon material and the mass percentage content W2 of the silicon-oxygen material are within the above range, it is beneficial to give play to the high specific capacity advantage of the silicon-carbon material, and it is also beneficial to give play to the low expansion stress and pore-filling ability of the silicon-oxygen material, improving the volumetric energy density of the lithium-ion battery while taking into account the electrochemical performance of the lithium-ion battery.
[0032] In one embodiment of the present application, based on the mass of the silicon-carbon material, the mass percentage of silicon in the silicon-carbon material is 40% to 51%, and the mass percentage of carbon in the silicon-carbon material is 45% to 57%. For example, the mass percentage of silicon in the silicon-carbon material can be 40%, 41%, 43%, 45%, 47%, 49%, 51%, or a range consisting of any two of these values; the mass percentage of carbon in the silicon-carbon material can be 45%, 47%, 49%, 51%, 53%, 55%, 57%, or a range consisting of any two of these values. When the mass percentages of carbon and silicon in the silicon-carbon material are within the above range, silicon can react with Li ions to alloy to provide capacity for the negative electrode, and the carbon skeleton can provide attachment sites for silicon, thereby enhancing the conductivity of the silicon-carbon material and constraining the volume expansion of silicon during the alloying process. Appropriate silicon and carbon content can improve the specific capacity of the silicon-carbon material while giving the silicon-carbon material good expansion properties.
[0033] In one embodiment of the present application, based on the mass of the silicon-oxygen material, the mass percentage of silicon in the silicon-oxygen material is 50% to 56%, and the mass percentage of oxygen in the silicon-oxygen material is 32% to 41%. For example, the mass percentage of silicon in the silicon-oxygen material can be 50%, 51%, 52%, 53%, 54%, 55%, 56%, or a range consisting of any two of these values; the mass percentage of oxygen in the silicon-oxygen material can be 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, or a range consisting of any two of these values. When the mass percentages of silicon and oxygen in the silicon-oxygen material are within the above ranges, during the lithium insertion process, Li can react with O and Si to generate Li2O and Li4SiO4 matrices surrounding Li x The area around the Si core can act as a rapid diffusion channel for lithium ions and effectively release the stress caused by expansion. The appropriate silicon and oxygen content is beneficial to improving the cycle performance, expansion performance and rate performance of lithium-ion batteries.
[0034] In one embodiment of the present application, in the Raman spectrum of the silicon-based material, I A Indicates 521cm in the Raman spectrum -1 ±15cm -1 The intensity of the peak A at B Indicates 480cm in the Raman spectrum -1 ±15cm -1 The intensity of the B peak at 0.85 A / I B <1.4. For example, I A / I B It can be 0.85, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4 or a range consisting of any two of these values. 521cm -1 The sharp Raman peak at 480cm represents crystalline silicon, while amorphous silicon has a relatively disordered structure. -1 A broad Raman peak is formed at 521 cm -1 and 480cm -1 The height ratio of the peaks at can reflect the content of silicon-carbon and silicon-oxygen materials and the ratio of crystalline silicon to amorphous silicon in silicon-based materials. A / I B Within the above range, the amorphous silicon in the silicon-carbon material has a smaller particle size and higher activity, which is beneficial to the capacity; while the crystalline silicon in the silicon-oxygen material has a larger particle size and stronger antioxidant ability, which is beneficial to improving the cycle performance, expansion performance and rate performance of lithium-ion batteries.
[0035] In one embodiment of the present application, the grain size D1 of the silicon microcrystals in the silicon-carbon material is less than 2.5 nm. For example, the grain size D1 of the silicon microcrystals in the silicon-carbon material can be 0.1 nm, 0.5 nm, 1 nm, 1.5 nm, 2 nm, 2.5 nm, or a range consisting of any two of these values. When the grain size D1 of the silicon microcrystals in the silicon-carbon material is within the above range, the deformation stress of the silicon-based material during the charge and discharge process can be buffered, and the structural stability of the silicon-based material can be improved.
[0036] In one embodiment of the present application, the ratio D1 / D2 of the grain size of silicon microcrystals in the silicon-carbon material to the grain size of silicon microcrystals in the silicon-oxygen material is 0.29 to 0.67. For example, the value of D1 / D2 can be 0.29, 0.31, 0.33, 0.35, 0.40, 0.51, 0.62, 0.67 or a range consisting of any two of the values. When the value of D1 / D2 is within the above range, it is conducive to more uniform insertion / extraction of lithium ions, improves the temperature coefficient of the battery, and thus improves the rate performance, cycle performance and expansion performance of the lithium-ion battery, while allowing the lithium-ion battery to have a high volume energy density.
[0037] In one embodiment of the present application, there is a crystallization peak of silicon in the X-ray diffraction pattern of the silicon-oxygen material, and the grain size D2 of the silicon microcrystals in the silicon-oxygen material is 1.6nm to 5nm. For example, the grain size D2 of the silicon microcrystals in the silicon-oxygen material can be 1.6nm, 2nm, 3nm, 4nm, 5nm, or a range consisting of any two of these values. When the grain size D2 of the silicon microcrystals in the silicon-oxygen material is within the above range, when the size of the silicon grains is within the above range, it is beneficial to improve the rate performance, cycle performance and expansion performance of the lithium-ion battery, while enabling the lithium-ion battery to have a high volume energy density.
[0038] In one embodiment of the present application, the compacted density of the silicon-based material is 1.0 g / cm 3 Up to 2.2g / cm 3 For example, the compacted density of silicon-based materials can be 1.0 g / cm 3 , 1.2g / cm 3 , 1.4g / cm 3 , 1.6g / cm 3 , 1.8g / cm 3 , 2g / cm 3 , 2.2g / cm 3 Or a range consisting of any two of the values. When the compaction density of the silicon-based material is within the above range, the volume energy density of the lithium-ion battery is improved.
[0039] In one embodiment of the present application, the silicon-carbon material can be prepared by the following method: (1) porous carbon (D50 is 4 μm to 10 μm, pore volume is 0.9 cm 3 / g, specific surface area is 1800m 2 / g) is dried, the treated porous carbon material is placed in a chemical vapor deposition furnace, the argon protective atmosphere is heated to 360°C to 450°C, 8% to 50% monosilane is used as a silicon source under a slightly positive gas pressure, 8L / min of argon is introduced as an inert gas, the total gas volume is set at a flow rate of 5L / min to 30L / min, and the reaction is continued for 5h to 12h, so that the elemental nano-silicon is adsorbed and deposited in the pores of the porous carbon. (2) In the same vapor deposition furnace, continue to raise the temperature to 500°C to 650°C under argon protective atmosphere, introduce a mixed gas containing argon gas with a carbon source gas ratio of 20% to 100% under a slightly positive gas pressure, set the total gas volume to a flow rate of 1L / min to 20L / min, and continue the reaction for 4h to 9h, and carbon deposition occurs on the outer surface of the porous carbon deposited with single-element nano-silicon and forms a carbon coating layer; the carbon source gas is acetylene, propyne and other alkynes, ethylene, propylene and other alkanes and methane, hexane and other alkanes and their mixed gases. (3) The deposited sample obtained in step (2) is ground and sieved with 400 mesh to obtain a final silicon-carbon material with a D150 of 4μm to 10μm.
[0040] In one embodiment of the present application, the silicon-oxygen material can be prepared by the following method: after mixing SiO2 and Si uniformly, place them in the evaporation chamber of a deposition furnace, heat them to 1000°C to 1400°C for the first deposition, collect the deposited SiO blocks in the deposition chamber, and obtain a silicon-oxygen precursor with a D50 of 0.8μm to 3.5μm after crushing, grading, etc. The silicon-oxygen precursor is placed in a carbon source gas flow with a flow rate of 2L / min to 6L / min and an argon gas mixture with a flow rate of 2L / min to 7L / min, control the reaction system to heat up to 500°C to 1000°C at a heating rate of 2°C / min to 6°C / min, keep warm for 3h to 7h, deposit amorphous carbon on the surface of the silicon-oxygen precursor, and obtain a silicon-oxygen material with a D250 of 0.8μm to 3.5μm.
[0041] In one embodiment of the present application, the silicon-based material can be prepared by the following method: weigh the silicon-carbon material and the silicon-oxygen material according to a mass percentage W1 / W2 of 2.9 to 16. Then, add ball milling beads to the vibration screen and vibrate for 3 hours to evenly mix the silicon-carbon and silicon-oxygen materials.
[0042] In one embodiment of the present application, the grain size of silicon microcrystals in the silicon-carbon material can be regulated by the reaction temperature of the porous carbon material reacting with the mixed gas of argon and silicon source gas in the chemical vapor deposition furnace and the deposition temperature in the argon atmosphere. For example, when the reaction temperature of the porous carbon material reacting with the mixed gas of argon and silicon source gas in the chemical vapor deposition furnace and the deposition temperature in the argon atmosphere are within the range of the above-mentioned preparation process, when the reaction temperature of the porous carbon material reacting with the mixed gas of argon and silicon source gas in the chemical vapor deposition furnace and the deposition temperature in the argon atmosphere increase, the grain size of silicon microcrystals in the silicon-carbon material increases, and when the reaction temperature of the porous carbon material reacting with the mixed gas of argon and silicon source gas in the chemical vapor deposition furnace and the deposition temperature in the argon atmosphere decrease, the grain size of silicon microcrystals in the silicon-carbon material decreases.
[0043] In one embodiment of the present application, the mass percentage of silicon in the silicon-carbon material can be regulated by the reaction time of the porous carbon material reacting with the mixed gas of argon and silicon source gas in the chemical vapor deposition furnace. For example, when the reaction time of the mixed gas reaction of argon and silicon source gas is within the range in the above-mentioned preparation process, when the reaction time of the mixed gas reaction of argon and silicon source gas increases, the mass percentage of silicon in the silicon-carbon material increases, and when the reaction time of the mixed gas reaction of argon and silicon source gas decreases, the mass percentage of silicon in the silicon-carbon material decreases.
[0044] In one embodiment of the present application, the grain size of silicon microcrystals in the silicon-oxygen material can be regulated by the reaction temperature of the silicon-oxygen precursor in the mixture of carbon source gas flow and argon gas. For example, when the reaction temperature of the silicon-oxygen precursor in the mixture of carbon source gas flow and argon gas is within the range in the above-mentioned preparation process, when the reaction temperature of the silicon-oxygen precursor in the mixture of carbon source gas flow and argon gas increases, the grain size of silicon microcrystals in the silicon-oxygen material increases, and when the reaction temperature of the silicon-oxygen precursor in the mixture of carbon source gas flow and argon gas decreases, the grain size of silicon microcrystals in the silicon-oxygen material decreases.
[0045] In one embodiment of the present application, the mass percentage of silicon in the silicon-oxygen material can be regulated by regulating the mass ratio of SiO2 and Si during the preparation process. When the mass ratio of SiO2 and Si increases, the mass percentage of silicon in the silicon-oxygen material decreases, and when the mass ratio of SiO2 and Si decreases, the mass percentage of silicon in the silicon-oxygen material increases.
[0046] The second aspect of the present application provides an electrochemical device, which includes a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte. The negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector, and the negative electrode material layer includes the silicon-based material in any of the aforementioned embodiments.
[0047] In the present application, the negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. The above-mentioned "negative electrode material layer disposed on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be disposed on one surface of the negative electrode current collector along its own thickness direction, or can be disposed on two surfaces of the negative electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of the surface of the negative electrode current collector, or it can be a partial area of the surface of the negative electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved.
[0048] The present application has no particular limitation on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate covered with a conductive metal, or a composite current collector. For example, the composite current collector may be a lithium-copper composite current collector, a carbon-copper composite current collector, a nickel-copper composite current collector, a titanium-copper composite current collector, etc.
[0049] In some embodiments of the present application, the negative electrode material layer may also include a conductive agent and a binder. The present application does not particularly limit the types of the conductive agent and the binder, as long as the purpose of the present application can be achieved. For example, the conductive agent may include but is not limited to at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials or conductive polymers, and the conductive carbon black may include but is not limited to at least one of acetylene black or Ketjen black. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The above-mentioned metal materials may include but are not limited to metal powders and / or metal fibers. Specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymers may include but are not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole. The present application does not particularly limit the mass ratio of the negative electrode active material, the conductive agent and the binder in the negative electrode material layer. Those skilled in the art may select according to actual needs as long as the purpose of the present application can be achieved.
[0050] The present application has no particular limitation on the binder as long as the purpose of the present application can be achieved. For example, the binder may include but is not limited to at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyimide, polyamide-imide, styrene-butadiene rubber or polyvinylidene fluoride.
[0051] In some embodiments of the present application, a conductive agent, a binder and a thickener may also be included. The present application has no particular restrictions on the types of conductive agents and thickeners, as long as the purpose of the present application can be achieved. For example, the conductive agent and the binder may be at least one of the above conductive agents and the above binders. The thickener may include but is not limited to at least one of sodium carboxymethyl cellulose or lithium carboxymethyl cellulose. The present application has no particular restrictions on the mass ratio of the negative electrode active material, the conductive agent, the binder and the thickener in the negative electrode material layer. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved.
[0052] The present application has no particular limitation on the thickness of the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode material layer is 30 μm to 200 μm.
[0053] The present application has no particular limitation on the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 4 μm to 15 μm.
[0054] Optionally, the negative electrode plate may further include a conductive layer, and the conductive layer is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, and it may be a conductive layer commonly used in the art. For example, the conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, and it may be at least one of the above conductive agent and the above binder.
[0055] In the present application, the lithium-ion battery also includes a positive electrode plate, which includes a positive electrode collector and a positive electrode material layer disposed on at least one surface of the positive electrode collector. The above-mentioned "positive electrode material layer disposed on at least one surface of the positive electrode collector" means that the positive electrode material layer can be disposed on one surface of the positive electrode collector along its own thickness direction, or on two surfaces of the positive electrode collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of the surface of the positive electrode collector, or it can be a partial area of the surface of the positive electrode collector. This application has no special restrictions, as long as the purpose of this application can be achieved.
[0056] The present application has no particular limitation on the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector).
[0057] The positive electrode material layer includes a positive electrode active material. The present application has no particular limitation on the positive electrode active material as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include but is not limited to lithium nickel cobalt manganese oxide (such as NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganese oxide, lithium iron manganese phosphate, lithium nickel titanate, lithium manganese cobalt oxide, lithium nickel manganese aluminum oxide, lithium vanadium phosphate, lithium cobalt phosphate, lithium manganese phosphate, lithium iron manganese phosphate, lithium iron silicate, lithium vanadium silicate, lithium cobalt silicate, lithium manganese silicate, spinel lithium manganese oxide, spinel lithium nickel manganese oxide or lithium titanate.
[0058] The positive electrode material layer may also include a conductive agent and a binder. The present application does not particularly limit the types of the conductive agent and the binder, as long as the purpose of the present application can be achieved. For example, it may be at least one of the above conductive agent and the above binder. The present application does not particularly limit the mass ratio of the positive electrode active material, the conductive agent, and the binder in the positive electrode material layer. Those skilled in the art can select according to actual needs, as long as the purpose of the present application can be achieved.
[0059] The present application has no particular limitation on the thickness of the positive electrode current collector and the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode current collector is 5 μm to 20 μm, and the thickness of the positive electrode material layer is 30 μm to 120 μm.
[0060] Optionally, the positive electrode sheet may further include a conductive layer, which is located between the positive electrode current collector and the positive electrode material layer. The composition of the conductive layer is not particularly limited, and it can be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, for example, it can be at least one of the above conductive agent and the above binder.
[0061] In the present application, the lithium-ion battery also includes a separator. The present application has no particular restrictions on the separator, as long as the purpose of the present application can be achieved. For example, the material of the separator may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or aramid. The type of separator may include at least one of a woven membrane, a non-woven membrane, a microporous membrane, a composite membrane, a rolled membrane or a spun membrane.
[0062] In some embodiments of the present application, the isolation film may include a substrate layer and a surface treatment layer. The substrate layer may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used.
[0063] Optionally, a surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic layer.
[0064] In some embodiments of the present application, the inorganic layer includes inorganic particles and a binder. The present application is not particularly limited to inorganic particles, such as inorganic particles can include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application is not particularly limited to binders, such as binders can be at least one of the above-mentioned binders. In some embodiments of the present application, the polymer layer includes polymers, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymers, polyacrylic acid, polyacrylates, polyvinyl pyrrolidone, polyvinyl ether or polyvinylidene fluoride or poly (vinylidene fluoride-hexafluoropropylene).
[0065] In the present application, there is no particular limitation on the thickness of the isolation film, as long as the purpose of the present application can be achieved. For example, the thickness of the isolation film may be 3 μm to 30 μm.
[0066] The present application has no particular restrictions on lithium salts, as long as the purpose of the present application can be achieved. For example, the lithium salt may include but is not limited to at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, Li2SiF6, lithium bis(oxalatoborate) (LiBOB) or lithium difluoroborate. The present application has no particular restrictions on the content of lithium salts in the electrolyte, as long as the purpose of the present application can be achieved.
[0067] The present application has no particular limitation on the non-aqueous solvent as long as the purpose of the present application can be achieved. For example, the non-aqueous solvent may include but is not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents.
[0068] The carbonate compound may include but is not limited to at least one of a linear carbonate compound, a cyclic carbonate compound or a fluorinated carbonate compound. The linear carbonate compound may include but is not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or methyl ethyl carbonate (MEC). The cyclic carbonate compound may include but is not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The fluorinated carbonate compound may include, but is not limited to, at least one of fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The above-mentioned carboxylate compound may include, but is not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone, or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate. The present application has no particular restrictions on the content of the non-aqueous solvent in the electrolyte, as long as the purpose of the present application can be achieved.
[0069] The lithium-ion battery also includes a shell for accommodating a positive electrode plate, a separator, a negative electrode plate and an electrolyte, as well as other components known in the field of lithium-ion batteries, and this application does not limit the above-mentioned other components. This application does not particularly limit the shell, and it can be a shell known in the art, as long as the purpose of this application can be achieved. For example, the shell can be a hard shell or a flexible shell. The material of the hard shell can be metal, and this application does not limit the type of metal. A metal hard shell known in the art can be used, as long as the purpose of this application can be achieved. The flexible shell can be a metal plastic film, such as an aluminum plastic film, a steel plastic film, etc.
[0070] A third aspect of the present application provides an electronic device, which includes the electrochemical device in any of the aforementioned embodiments.
[0071] The electronic device of the present application is not particularly limited, and it can be used for any electronic device known in the prior art. In some embodiments, the electronic device can include but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.
[0072] Example
[0073] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0074] Test methods and equipment
[0075] Test of average particle size of silicon-carbon materials and average particle size of silicon-oxygen materials
[0076] The negative electrode plate was processed by an ion polisher (IB-09010CP) to obtain a cross-section of the negative electrode material layer along the thickness direction, and a scanning electron microscope (ZEISS SEM (Sigma-02-33) (0.1-30KV)) was used to simultaneously shoot EDS and background scattering of the cross-section, wherein, in the background scattering field of view, the color of the silicon-based material was brighter than that of the graphite particles; in the EDS test, a total of 250 particles of the silicon-carbon material and the silicon-oxygen material were tested, respectively, and the distance between the two farthest points on the cross-section of each particle was tested, and the average value of the distance between the two farthest points on the cross-section of the 250 particles was calculated to obtain the average particle size of the silicon-carbon material and the average particle size of the silicon-oxygen material.
[0077] Testing of silicon, oxygen and carbon in silicon-carbon materials and silicon-oxygen materials
[0078] The content of silicon in silicon-carbon materials and silicon-oxygen materials (in wt%) was tested by ICP (inductively coupled plasma spectrometer) characterization method.
[0079] The carbon content in the silicon-carbon material and the oxygen content in the silicon-oxygen material were tested by EDS characterization (in wt%).
[0080] Raman testing of silicon-based materials
[0081] A region of 100 μm × 100 μm of silicon-based solid powder was selected, and the particles in the region were scanned using a laser microscopic confocal Raman spectrometer (Raman, HR Evolution, HORIBA Scientific Instruments Division). The laser wavelength of the Raman spectrometer was in the range of 532 nm to 785 nm, and the A peak and B peak of all particles in the region were obtained. The data were processed using LabSpec software to obtain the intensities of the A peak and B peak of each particle, which were recorded as I A ,I B , count the I of all particles in the area A and I B The Raman spectrum of the silicon-based material of Example 2-1 is as follows: Figure 1 shown.
[0082] Grain size measurement of silicon microcrystals
[0083] The silicon-carbon material and silicon-oxygen material are subjected to XRD test (Cu target Kα ray) by X-ray powder diffractometer (POWDIX600 / 300), and the grain size of silicon microcrystals can be obtained by calculating the peak near 28.5° using Scherrer formula.
[0084] Compaction density testing of silicon-based materials
[0085] Using the UTM7305 powder compaction density meter, a certain mass m of silicon-based material powder is weighed and placed in a compaction mold with a known radius (r). There is a metal cylinder on the top of the mold. After setting 5 tons of pressure and 10mm / min for 30s, the corresponding powder thickness H is read on the device. The density formula ρ = m / v, v = πr 2 ×H, the compacted density of the silicon-based material is calculated.
[0086] Silicon Carbon Material Gram Capacity Test
[0087] Assembling button half-cells: using silicon-based materials as negative electrode active materials, conductive carbon black as conductive agent, and sodium carboxymethyl cellulose as binder, the negative electrode active materials, conductive carbon black, and sodium carboxymethyl cellulose are fully mixed in an aqueous solution at a mass ratio of 84:10:6 to obtain a mixture slurry with a solid content of 25%, and the mixture slurry is evenly coated on a copper foil and dried to obtain a negative electrode sheet; in an argon-filled glove box (water content <10ppm, oxygen content <1ppm), ethylene carbonate (EC) and dimethyl carbonate (DMC) are evenly mixed at a volume ratio of 1:1, LiPF6 is slowly added to the mixed solution, and stirred evenly to obtain a non-aqueous electrolyte; a 10μm thick polypropylene film is used as an isolation membrane; the above-mentioned negative electrode sheet is used with a lithium sheet as a counter electrode, and the lithium sheet is assembled into a button half-cell in the glove box in the order of negative electrode sheet, isolation membrane, and lithium sheet. The half-cell assembled as above was subjected to charge and discharge tests on a LAND battery test system (LAND CT2001A). The half-cell test adopted an operating voltage range of 0.005V to 2.0V. The battery was discharged to 0.005V at a constant current of 0.05C, discharged to 0.005V at a constant current of 50μA, and allowed to stand for 30min. The battery was discharged to 0.005V at a constant current of 10μA, and allowed to stand for 5min. The battery was charged to 2.0V at a constant current of 0.05C, and allowed to stand for 5min. The charge capacity at the first charge voltage of 0.8V / the first discharge capacity was taken as the gram capacity of the silicon-carbon material.
[0088] Cyclic performance test
[0089] At a test temperature of 25℃ / 45℃, let the lithium-ion battery to be tested stand for 5 minutes, and record the initial thickness d0 of the lithium-ion battery. Charge the lithium-ion battery to 4.25V with a constant current of 3C, then charge to 4.4V with 2C, then charge to 4.50V with 1C, and then charge to 0.05C with a constant voltage of 4.50V, let stand for 5 minutes, and then discharge to 3.0V with a constant current of 0.5C, and record the discharge capacity C0 of the lithium-ion battery. After the above 3C step charge / 0.5C discharge charge and discharge cycle process is cycled 400 times, record the thickness d1 and discharge capacity C1 of the lithium-ion battery. The capacity retention rate of 400 cycles is characterized as the cycle performance of the lithium-ion battery, and the expansion rate of 400 cycles is characterized as the expansion performance of the lithium-ion battery. The capacity retention rate after 400 cycles (%) = C1 / C0×100%, the expansion rate after 400 cycles (%) = (d1-d0) / d0×100%.
[0090] Discharge rate test
[0091] At 25°C, the lithium-ion battery is discharged to 3.0V at 0.2C, left to stand for 5 minutes, charged to 4.50V at 0.5C, charged to 0.05C at 4.50V constant voltage and left to stand for 5 minutes, discharged to 3.0V at 0.2C, and the discharge capacity at this time is recorded as C0, left to stand for 5 minutes, charged to 4.50V at 0.5C, charged to 0.05C at 4.50V constant voltage and left to stand for 5 minutes, discharged to 3.0V at 2C, and the discharge capacity at this time is recorded as C1, and the ratio of the discharge capacity of the lithium-ion battery at 2C to 0.2C is characterized as the rate performance of the lithium-ion battery. Discharge rate (%) = C1 / C0×100%.
[0092] Lithium ion diffusion coefficient test
[0093] According to the method of the silicon-carbon material gram capacity test section above, the silicon-based materials in the embodiment and the comparative example are assembled into button-type half-cells. After the button-type half-cell is left at room temperature for 12 hours, it is discharged at a constant current of 0.1C until the voltage is less than or equal to 0.005V. After standing for 1 hour, if the voltage is greater than 0.005V, continue to discharge at a constant current of 0.1C until the voltage is less than or equal to 0.005V, and then stand for 1 hour. Perform constant current charging at 0.1C until the voltage is greater than or equal to 1.5V, and stand for 1 hour; if the voltage is less than 1.5V, continue to charge at a constant current of 0.1C until the voltage is greater than or equal to 1.5V, stand for 1 hour, and then perform constant current discharge at 0.1C until the voltage is less than or equal to 0.005V. Perform two cycles according to the above steps and the test is completed. The lithium ion diffusion coefficient is obtained according to the following calculation formula:
[0094]
[0095] Where m and M represent the material mass and molar mass of the active substance, respectively, and V m is the molar volume, τ is the relaxation time, A is the electrode surface area, ΔE s is the voltage change caused by the pulse, ΔE τ The voltage change during constant current charging and discharging.
[0096] 20% SOC DC impedance test
[0097] At 25°C, use a Xinwei charger (5V / 12A) to charge the lithium-ion battery at a constant current of 1C to 4.50V, then charge at a constant voltage of 4.50V to 0.05C and let stand for 5 minutes; then discharge at 0.5C to 3.0V and let stand for 5 minutes; charge at a constant current of 1C to 4.50V, then charge at a constant voltage of 4.50V to 0.05C and let stand for 120 minutes; discharge at 1C for 360s, let stand for 120 minutes, then discharge at 0.1C for 10s, repeat this step 11 times, and let stand for 20 minutes; take the eighth cycle, the DC impedance data at 20% SOC charge state.
[0098] Volumetric energy density test
[0099] In an environment of 25°C, the lithium-ion batteries in the embodiments and comparative examples are charged according to the following operation flow, and then discharged to obtain the discharge capacity of the lithium-ion battery: the lithium-ion battery is charged to 4.5V at a constant current of 0.7C, then charged to 0.05C at a constant voltage of 4.5V, left to stand for 5 minutes, discharged to 3.0V at a constant current of 0.2C, left to stand for 5 minutes, and the discharge capacity D is obtained. After the above lithium-ion battery is charged to 3.95V at a constant current of 0.7C, it is then charged to 0.05C at a constant voltage of 3.95V, and the length L, width W, and height H of the lithium-ion battery are tested with a laser thickness gauge to obtain the volume V=L×W×H of the lithium-ion battery. Its volume energy density (ED)=D / V, in units of Wh / L.
[0100] Example 1-1
[0101] <Preparation of Silicon Carbon Materials>
[0102] (1) For porous carbon (D50 is 7 μm, pore volume is 0.9 cm 3 / g, specific surface area is 1800m 2 / g) was dried, and the treated porous carbon material was placed in a chemical vapor deposition furnace. The argon protective atmosphere was heated to 420°C, and 10% monosilane was used as the silicon source under a slightly positive gas pressure. 8L / min of argon was introduced as an inert gas, and the total gas flow rate was set to 18L / min to continue the reaction for 9h, so that the elemental nano-silicon was adsorbed and deposited in the pores of the porous carbon.
[0103] (2) In the same vapor deposition furnace, the temperature is continued to be raised to 550°C under an argon protective atmosphere, and a mixed gas containing argon gas with a carbon source gas ratio of 50% is introduced under a slightly positive gas pressure. The total gas flow rate is set to 5 L / min and the reaction is continued for 5.6 hours. Carbon deposition occurs on the outer surface of the porous carbon on which the elemental nanosilicon is deposited and a carbon coating layer is formed. The carbon source gas is alkynes such as acetylene and propyne, olefins such as ethylene and propylene, and alkanes such as methane and hexane, as well as mixed gases thereof.
[0104] (3) The sediment sample obtained in step (2) was ground and sieved through 400 mesh to obtain a final silicon-carbon material with a D150 of 7.1 μm.
[0105] <Preparation of Silicon Oxygen Material>
[0106] 15kg of SiO2 and 7kg of Si were mixed evenly and placed in the evaporation chamber of the deposition furnace. After heating to 1300℃ for the first deposition, the deposited SiO blocks were collected in the deposition chamber. After crushing and grading, a silicon oxide precursor with a D50 of 2μm was obtained. The silicon oxide precursor was placed in a mixture of a carbon source gas flow with a flow rate of 4L / min and an argon gas with a flow rate of 5L / min. The reaction system was controlled to heat up to 700℃ at a heating rate of 5℃ / min and kept warm for 5h. Amorphous carbon was deposited on the surface of the silicon oxide precursor to obtain a silicon oxide material with a D250 of 2.1μm.
[0107] <Preparation of Silicon-Based Materials>
[0108] The silicon-carbon material and the silicon-oxygen material prepared above were weighed according to a mass percentage of W1 / W2=9. Then, ball mill beads were added to a vibrating screen and vibrated for 3 hours to uniformly mix to obtain a silicon-based material.
[0109] <Preparation of positive electrode sheet>
[0110] The positive electrode active material LiCoO2, the conductive agent conductive carbon black, and the binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 95:2.5:2.5, and N-methylpyrrolidone (NMP) is added as a solvent to prepare a slurry with a solid content of 75wt%, and the positive electrode slurry is obtained after vacuum stirring. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 13μm, and dried at 120°C to obtain a positive electrode sheet coated with a single-sided positive electrode material layer. Then repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a double-sided positive electrode material layer. After drying at 120°C, cold pressing is performed, and then cutting and welding of the pole ears are performed to obtain a standard positive electrode sheet for standby use, with a water content of ≤200ppm.
[0111] <Preparation of negative electrode sheet>
[0112] Artificial graphite, the silicon-based material prepared above, conductive carbon black Super-P, and binder polyacrylic acid (PAA) are mixed in a mass ratio of 88:9:1:2, and deionized water is added as a solvent to prepare a slurry with a solid content of 40wt% and a viscosity of 7000Pa·s. The negative electrode slurry is obtained after being stirred evenly by a vacuum mixer. The negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 10μm, and dried at 120°C to obtain a negative electrode sheet coated with a negative electrode material layer on one side. Then repeat the above steps on the other surface of the copper foil to obtain a negative electrode sheet coated with a negative electrode material layer on both sides. After drying at 120°C, cold pressing is performed, and then the sheet is cut and the tabs are welded to obtain a negative electrode sheet for standby use, with a water content of ≤200ppm.
[0113] <Preparation of Electrolyte>
[0114] In a dry argon environment, ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) are mixed in a mass ratio of 1:1:1 to obtain a non-aqueous solvent, and then lithium salt LiPF6 and fluoroethylene carbonate (FEC) are added to the non-aqueous solvent and mixed to obtain an electrolyte. Among them, based on the mass of the electrolyte, the mass percentage of LiPF6 is 12.5%, the mass percentage of FEC is 4.5%, and the rest is the non-aqueous solvent.
[0115] <Isolation film>
[0116] A polyethylene / polypropylene composite film with a thickness of 8 μm was used as the isolation membrane.
[0117] <Preparation of lithium-ion batteries>
[0118] The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked in order, with the separator placed between the positive electrode sheet and the negative electrode sheet to play a role of isolation, and then wound to obtain an electrode assembly. The electrode assembly is placed in an aluminum-plastic film packaging bag, and the moisture is removed at 80°C, and the prepared electrolyte is injected, and a lithium-ion battery is obtained through vacuum packaging, standing, formation, degassing, and trimming.
[0119] Example 1-2 to Example 1-8
[0120] Except that D150 and D250 are adjusted according to Table 1 in <Preparation of silicon-carbon material> and <Preparation of silicon-oxygen material>, and D150 / D250 is changed accordingly, the rest is the same as Example 1-1.
[0121] Example 2-1 to Example 2-5
[0122] Except that the mass percentage W1 of silicon-carbon material based on silicon-based material and the mass percentage W2 of silicon-oxygen material based on silicon-based material are adjusted according to Table 2 in <Preparation of silicon-carbon material> and <Preparation of silicon-oxygen material>, and W1 / W2 changes accordingly, the rest is the same as Example 1-1.
[0123] Example 3-1 to Example 3-8
[0124] Except for adjusting the mass percentage of silicon element in the silicon-carbon material, the grain size of silicon microcrystals in the silicon-carbon material, the mass percentage of silicon element and oxygen element in the silicon-oxygen material, and the grain size of silicon microcrystals in the silicon-oxygen material according to Table 3 in <Preparation of silicon-carbon material> and <Preparation of silicon-oxygen material>, the rest is the same as Example 1-1.
[0125] Comparative Example 1
[0126] Except that D150 is adjusted to be greater than 10 μm, D250 is adjusted to be less than 0.8 μm, and D150 / D250 is greater than 10 in <Preparation of silicon-carbon material> and <Preparation of silicon-oxygen material>, the rest is the same as Example 1-1.
[0127] Comparative Example 2
[0128] Except that D150 and D250 are adjusted so that D150 / D250 is less than 1.8 in <Preparation of silicon-carbon material> and <Preparation of silicon-oxygen material>, the rest is the same as Example 1-1.
[0129] The preparation parameters and performance parameters of each embodiment and comparative example are shown in Table 1, Table 2 and Table 3.
[0130]
[0131] It can be seen from Examples 1-1 to 1-8 and Comparative Examples 1 to 2 that when D150 is 4 μm to 10 μm and D150 / D250 is 1.8 to 10, the 20% state of charge DC impedance of the silicon-based material is small, the 2C / 0.2C discharge rate is high, the obtained lithium-ion battery has a high volume energy density, and the cycle performance and expansion performance at 25°C / 45°C are good. In Comparative Examples 1 and 2, D150 / D250 is not within the scope of the present application, the obtained lithium-ion battery has a low volume energy density, and the cycle performance and expansion performance at 25°C / 45°C are poor, which shows that the volume energy density, cycle performance and expansion performance of the lithium-ion battery using the silicon-based material of the present application are improved.
[0132] It can be seen from Examples 1-1 to 1-8 that when D150 is 4 μm to 10 μm, D150 / D250 is 1.8 to 10, D250 is 0.8 μm to 3.5 μm, and / or the powder compaction density of the silicon-based material is 1.0 g / cm3 to 2.2 g / cm 3 When the mass is from 2.2 g / cm to 2.2 g / cm, the DC impedance of the silicon-based material at 20% state of charge is small, the 2C / 0.2C discharge rate is high, the volume energy density of the obtained lithium-ion battery is high, and the cycling performance and swelling performance at 25°C / 45°C are good, indicating that the volume energy density, cycling performance and swelling performance of the lithium-ion battery are improved.
[0133] Table 2
[0134]
[0135] It can be seen from Examples 1-1, 2-1 to 2-5 that when the mass percentage content W1 of the silicon-carbon material is 70% to 95%, the mass percentage content W2 of the silicon-oxygen material is 5% to 30%, 2.9 < W1 / W2 < 16, and / or 0.85 < I A / I B < 1.4, the volume energy density of the obtained lithium-ion battery is high, and the cycling performance and swelling performance at 25°C / 45°C are good, indicating that the volume energy density, cycling performance and swelling performance of the lithium-ion battery are improved.
[0136] Table 3
[0137]
[0138] Note: In Table 3, W3 represents the mass percentage content of silicon element in the silicon-carbon material, W4 represents the mass percentage content of silicon element in the silicon-oxygen material, W5 represents the mass percentage content of oxygen element in the silicon-oxygen material, D1 represents the grain size of silicon microcrystals in the silicon-carbon material, and D2 represents the grain size of silicon microcrystals in the silicon-oxygen material.
[0139] It can be seen from Examples 1-1, 3-1 to 3-8 that when the mass percentage content of silicon element in the silicon-carbon material is 40% to 51%, the mass percentage content of silicon element in the silicon-oxygen material is 50% to 56%, the mass percentage content of oxygen element in the silicon-oxygen material is 32% to 41%, the ratio of the grain size of silicon microcrystals in the silicon-carbon material to the grain size of silicon microcrystals in the silicon-oxygen material is 0.29 to 0.67, the grain size of silicon microcrystals in the silicon-carbon material is less than 2.5 nm, and / or the grain size of silicon microcrystals in the silicon-oxygen material is 1.6 nm to 5 nm, the 0.8V gram capacity of the silicon-carbon material is high, the 2C / 0.2C discharge rate of the silicon-based material is high, the volume energy density of the obtained lithium-ion battery is high, and the cycling performance and swelling performance at 25°C / 45°C are good, indicating that the volume energy density, cycling performance and swelling performance of the lithium-ion battery are improved.
[0140] The terms "comprises," "comprising," or any other variations thereof are intended to cover a non-exclusive inclusion such that a process, method, or article that comprises a list of elements includes not only those elements but also includes other elements not expressly listed or that are inherent to such process, method, or article.
[0141] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
[0142] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the principles of the present application shall be included in the scope of protection of the present application.
Claims
1. A silicon-based material, the silicon-based material comprising a silicon-carbon material and a silicon-oxygen material, the average particle size D150 of the silicon-carbon material and the average particle size D250 of the silicon-oxygen material satisfying: 1.8 < D150 / D250 < 10, wherein, D150 is 4μm to 10μm.
2. The silicon-based material according to claim 1, wherein The average particle size D250 of the silicon-oxygen material is 0.8 μm to 3.5 μm.
3. The silicon-based material according to claim 1, wherein The average particle size D150 of the silicon-carbon material is 6 μm to 8 μm, and the average particle size D250 of the silicon-oxygen material is 1.5 μm to 2.5 μm.
4. The silicon-based material according to claim 1, wherein Based on the mass of the silicon-based material, the mass percentage of the silicon-carbon material is W1, the mass percentage of the silicon-oxygen material is W2, 2.9 <W1 / W2<16。 5. The silicon-based material according to claim 4, wherein Based on the mass of the silicon-based material, the mass percentage W1 of the silicon-carbon material is 70% to 95%, and the mass percentage W2 of the silicon-oxygen material is 5% to 30%.
6. The silicon-based material according to claim 1, wherein Based on the mass of the silicon-carbon material, the mass percentage of the silicon element in the silicon-carbon material is 40% to 51%, and the mass percentage of the carbon element in the silicon-carbon material is 45% to 57%; based on the mass of the silicon-oxygen material, the mass percentage of the silicon element in the silicon-oxygen material is 50% to 56%, and the mass percentage of the oxygen element in the silicon-oxygen material is 32% to 41%.
7. The silicon-based material according to claim 1, wherein In the Raman spectrum of the silicon-based material, I A Indicates 521cm in the Raman spectrum -1 ±15cm -1 The intensity of the peak A at B Indicates 480cm in the Raman spectrum -1 ±15cm -1 The intensity of the B peak at 0.85 A / I B <1.4. 8. The silicon-based material according to claim 1, wherein The grain size of silicon microcrystals in the silicon-carbon material is less than 2.5 nm; there is a crystallization peak of silicon in the X-ray diffraction spectrum of the silicon-oxygen material, and the grain size of silicon microcrystals in the silicon-oxygen material is 1.6 nm to 4.5 nm.
9. The silicon-based material according to claim 8, wherein: The ratio of the grain size of silicon microcrystals in the silicon-carbon material to the grain size of silicon microcrystals in the silicon-oxygen material is 0.29 to 0.
67.
10. The silicon-based material according to claim 1, wherein The compacted density of the silicon-based material is 1.0 g / cm 3 Up to 2.2g / cm 3 .
11. An electrochemical device, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet comprises a negative electrode collector and a negative electrode material layer arranged on at least one surface of the negative electrode collector, and the negative electrode material layer comprises the silicon-based material according to any one of claims 1 to 10. 12 . An electronic device comprising the electrochemical device according to claim 11 .
Citation Information
Patent Citations
Negative active material, negative plate and battery
CN118431448A
Electrochemical device and electronic device
CN118435375A
Negative electrode plate, electrochemical device comprising negative electrode plate, and electronic device
WO2022205143A1
Negative electrode plate, and electrochemical device and electronic device comprising negative electrode plate
WO2024050813A1
